(untitled) (New York, 1985)
This collection of essays offers a challenge to the conventional business wisdom that advocates phasing out "mature" industries in favour of developing new, high-tech ones. It urges managers to develop new skills to understand the changing competitive environment and take appropriate action. The book outlines the altered terms of competition confronting industries exposed to price and/or quality attacks from abroad, and the conditions under which mature industries have been revitalized.
Keywords: Industrial management,Quản lý công nghiệp